2004
DOI: 10.1093/condor/106.2.390
|View full text |Cite
|
Sign up to set email alerts
|

You Can't Judge a Pigment by its Color: Carotenoid and Melanin Content of Yellow and Brown Feathers in Swallows, Bluebirds, Penguins, and Domestic Chickens

Abstract: The two main pigment types in bird feathers are the red, orange, and yellow carotenoids and the black, gray, and brown melanins. Reports conflict, however, regarding the potential for melanins to produce yellow colors or for carotenoids to produce brown plumages. We used high-performance liquid chromatography to analyze carotenoids and melanins present in the yellow and brown feathers of five avian species: Eastern Bluebirds (Sialia sialis), Barn Swallows (Hirundo rustica), King Penguins (Aptenodytes patagonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 27 publications
6
79
0
Order By: Relevance
“…This shows that the yellow-orange skin colour of common lizards stem from carotenoids and not from melanins or pteridins, neither of which are soluble in acetone [61]. In total, the skin contained 54.09 µg±4.67 SE carotenoids per gram tissue (5.144 µg±0.467 SE carotenoids per gram fresh weight), including lutein, zeaxanthin, astaxanthin, and canthaxanthin.…”
Section: Resultsmentioning
confidence: 89%
“…This shows that the yellow-orange skin colour of common lizards stem from carotenoids and not from melanins or pteridins, neither of which are soluble in acetone [61]. In total, the skin contained 54.09 µg±4.67 SE carotenoids per gram tissue (5.144 µg±0.467 SE carotenoids per gram fresh weight), including lutein, zeaxanthin, astaxanthin, and canthaxanthin.…”
Section: Resultsmentioning
confidence: 89%
“…the throat ‘bib’ of the house sparrow Passer domesticus ), and that we are just now beginning to understand the control agents and signaling function of phaeomelanin‐containing traits (e.g. in barn swallows and eastern bluebirds Sialia sialis ; McGraw et al 2004, Siefferman and Hill 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Parrots, for example, use a unique class of polyenal lipochromes to generate their spectrum of plumage colors (Stradi et al 2001). McGraw et al (2004) showed that the yellow downy plumage of domestic chicks Gallus domesticus and the yellow feathers of adult king Aptenodytes patagonica and macaroni Eudyptes chrysolophus penguins lack carotenoids and instead harbor as‐of‐yet uncharacterized fluorescent compounds. Still others have shown that melanin pigments are responsible for the buff‐yellow feather colors in certain breeds of chicken (Frank 1939), turkey Meleagris gallopavo (Somes and Smyth 1965) and quail Coturnix japonica (Shiojiri et al 1999).…”
mentioning
confidence: 99%
“…Because hue (calculated as maximum slope) of the chestnut breast feathers expressed very little variation among males, we do not report hue for breast coloration. Unlike the analyses in Siefferman and Hill (2003), we analyzed the plumage color of the rump, tail, and breast feathers separately because 1) yearling and older birds molt tail feathers at different times, and 2) the UV‐blue coloration of the rump and tail is produced by the feather nanostructure (Shawkey et al 2003) while the chestnut coloration of the breast is caused by the deposition of melanin pigments (McGraw et al 2004).…”
Section: Methodsmentioning
confidence: 99%